Health Care Decisions in Social Care Settings: General Regulation and Interpretation in Cpt’s Jurisprudence - Kadile, Laura (Medicine, Law & Society, 2023)
The Committee for the Prevention of Torture and Inhuman Treatment is a body of the Council of Europe that organises visits to places of detention such as social care homes in order to assess how persons deprived of their liberty are treated. This means that in practice people are not free to leave the institution and are therefore de facto deprived of liberty. In such situations, people with disabilities are particularly vulnerable and have limited capacity to make decisions about medical treatment and care. As the number of such persons increases, and in order to ensure protection under international law, the results of the empirical study indicate the need to provide immediate assistance to residents in safeguarding their rights to self-determination or private autonomy and legal interests in making health care decisions in social care settings. For example, involving the resident in consenting to treatment or establishing a decision-making assessment procedure.